Implementation of sustainable public procurement practices and policies: A sorting framework. Issue 3 (1st March 2016) - Prier, Eric; Schwerin, Edward; McCue, Clifford P.
Abstract : In general, there are many disincentives standing in the way of promoting change in public procurement practices by government agencies. Because engaging in sustainable purchasing requires some level of entrepreneurialism and risk-taking, a sorting framework is adopted to gauge whether some organizations are systematically more likely to pursue sustainable public purchasing (SPP) efforts than others. One-way analysis of variance and other methods are applied to a survey of public procurement practitioners across over 300 governments in the U.S. Results strongly suggest that agencies of various scope and reach tend to abstain from aggressively pursuing SPP efforts. However, when they do employ SPP, these efforts tend to be quite variable across and within levels of government and organizational size. In an effort to bridge theory with empirical data, a strong case can be made that the current state of SPP in the United States is the result of random and very cautious experimentation with little systematic pattern to SPP adoption.